Beyond food promotion: a systematic review on the influence of the food industry on obesity-related dietary behaviour among children - Sonntag, Diana; Schmidt, Burkhard (Nutrients, 2015)
An increased consumption of energy-dense, nutrient-poor food and beverages as a result of a changing obesogenic environment contributes substantially to the increasing prevalence of childhood overweight and obesity. This paper reviews the nature and extent of food industry influences which expose children to commercial influences and thus might affect unhealthy dietary behaviour and finally contributes to obesity. A systematic search of nine electronic databases (including PubMed, PsycINFO, EconLit) and reference lists of original studies and reviews using key search terms identified 1900 articles. Of these only thirty-six articles met the inclusion and quality criteria. A narrative synthesis of the reviewed studies revealed six key obesogenic environments by which the food industry possibly influences obesity-related dietary behaviours in young children. These were schools, retailers, mass media “television”, mass media “internet”, home and promotional campaigns. Identifying these obesogenic environments is critical for monitoring and controlling the food industry, the development of effective environmental-level interventions to prevent childhood overweight and obesity and to identify knowledge gaps to be addressed in future research to support informed decisions of policy makers.